The evolution of the civil service a progress report - Butler, Robin (1993)
The author have chosen the word `evolution' deliberately because he wants to convey the idea of the mutation of a body into something different over a period in response to external changes in the environment in which it operates. Evolution is also an apt word because it conveys that the changes have been taking place over a long period and are likely to last for a long time. The author sometimes asked what the final shape of the civil service will be, in tones that imply that the Head of the Civil Service ought to know the answer to that question which he does not know well
Keywords: Public administration; Bureaucracy; Civil service